2023
DOI: 10.1002/jsfa.12820
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil phosphatase activity and soil phosphorus fractions to the application of chloropicrin and azoxystrobin in ginger cultivation

Abstract: BACKGROUNDSoil fumigation can change soil nutrient cycling processes by affecting soil beneficial microorganisms, which is a key issue for soil fertility. However, the effect of combined application of fumigant and fungicide on soil phosphorus (P) availability remains largely unclear. We investigated the effects of the fumigant chloropicrin (CP) and the fungicide azoxystrobin (AZO) on soil phosphatase activity and soil P fractions in ginger production using a 28‐week pot experiment with six treatments: control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, Huang et al (2020a;2020b) found that soil fumigation using chloropicrin and dazomet increased soil active P (H 2 O-P, NaHCO 3 -Pi and NaHCO 3 -Po) in the early stage of the culture (<7days). Wang et al (2023) also found that chloropicrin fumigation significantly increased the proportions of soil labile P fractions (Resin-P+NaHCO 3 -Pi + NaHCO 3 -Po) to total P across 28 weeks of ginger growth. However, the death of PSMs may reduce P-cycle related functional bacterial genes, and slow down the secretion of related phosphatase enzymes, which may arrest the mineralization of soil organic P. Both Huang et al (2020a;2020b) and Wang et al (2023) found that soil fumigation significantly reduced the phoC and phoD gene copy number, and related acid and alkaline phosphatase activities.…”
Section: Soil Phosphorus Cyclingmentioning
confidence: 74%
See 4 more Smart Citations
“…For example, Huang et al (2020a;2020b) found that soil fumigation using chloropicrin and dazomet increased soil active P (H 2 O-P, NaHCO 3 -Pi and NaHCO 3 -Po) in the early stage of the culture (<7days). Wang et al (2023) also found that chloropicrin fumigation significantly increased the proportions of soil labile P fractions (Resin-P+NaHCO 3 -Pi + NaHCO 3 -Po) to total P across 28 weeks of ginger growth. However, the death of PSMs may reduce P-cycle related functional bacterial genes, and slow down the secretion of related phosphatase enzymes, which may arrest the mineralization of soil organic P. Both Huang et al (2020a;2020b) and Wang et al (2023) found that soil fumigation significantly reduced the phoC and phoD gene copy number, and related acid and alkaline phosphatase activities.…”
Section: Soil Phosphorus Cyclingmentioning
confidence: 74%
“…Wang et al (2023) also found that chloropicrin fumigation significantly increased the proportions of soil labile P fractions (Resin-P+NaHCO 3 -Pi + NaHCO 3 -Po) to total P across 28 weeks of ginger growth. However, the death of PSMs may reduce P-cycle related functional bacterial genes, and slow down the secretion of related phosphatase enzymes, which may arrest the mineralization of soil organic P. Both Huang et al (2020a;2020b) and Wang et al (2023) found that soil fumigation significantly reduced the phoC and phoD gene copy number, and related acid and alkaline phosphatase activities. This in turn can further slow down the mineralization processes of organic P released from the dead microbes, which then results in an accumulation of soil organic P (especially labile NaHCO 3 -Po) in the fumigated soils (Wang et al 2023).…”
Section: Soil Phosphorus Cyclingmentioning
confidence: 74%
See 3 more Smart Citations